The CORE Model for Improving students behavior and learning outcomes the production technology development of Social Sciences Learning - Gilang Maulana Jamaludin; Muhammad Iqbal Al Ghozali; Rifki Fauzi (MUDARRISA: Jurnal Kajian Pendidikan Islam, 2020)
Social studies subjects are one of the subjects that are not liked because the learning context is too monotonous containing memorization and readings that make the learning process saturated.  This study aims to determine the increase in social studies activities and learning outcomes in the development of production technology by applying the Connecting Organizing Reflecting Extending (CORE) learning model.  This study used the Classroom Action Research (CAR) or Penelitian Tindakan Kelas (PTK) method by Kemmis and Mc.Taggart models.  The results of this study were in the first cycle of student activity aspects of visual activities 71.8% (good), aspects of oral activities 69.2% (good criteria), and aspects of listening activities 77% (good).  In the second cycle, there was an increase namely the students' activities visual aspects to 83.3% (very good), aspects of oral activities 81.4% (very good), and aspects of listening activities 83.3% (very good).  For the final test results, students also experienced an increase.  The magnitude of the increase in the percentage of mastery learning from the initial data to the first cycle increased from 46.1% to 69.2%, while from the first cycle to the second cycle an increase from 69.2% to 92.3% of students who completed.  Thus, it can be stated that the CORE model can improve student learning outcomes towards social studies learning on the material development of production technology in fourth-grade students at SDN Salamjajar, Cisitu District, Sumedang region.